Sex Education and Other Methods to Prevent Teen Pregnancies in the Bible Belt of the United States - van Hoff, Hannah (Trinity College (Dublin, Ireland). School of Education, 2021)
This systematic literature review is meant to answer the questions what are the factors affecting teen pregnancy rates in the United States, specifically in the Bible Belt region, and how can the United States change these factors to reduce these rates? The United States has an internationally high rate of teen pregnancy compared to similarly developed countries. The main factors found to cause these high teen pregnancy rates in the United States are a lack of contraceptive use, a lack of access to health care, and poverty, which can cause the other two factors to appear. Possible solutions to reducing the teen pregnancy rate in the United States include requiring comprehensive sex education in schools, creating a universal, free health care system, and giving poverty stricken teens the chance for a better future, either by reducing poverty in general, or providing avenues away from it. Obviously, the problem is much more nuanced, but the fact remains that reducing the high teen pregnancy rate in the United States is something that is possible and should be done.
Keywords: Science Education; Education